How to integrate "Brand image Design" kecheng into AIGC technology - Zhu, Heng (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of Artificial Intelligence Generated Content (AIGC) technology, its application in various fields is increasingly widespread. This study aims to explore how to integrate AIGC into the brand image course to improve teaching effectiveness and cultivate students’ innovative practical ability. By analyzing the characteristics and advantages of AIGC, combined with the teaching objectives and contents of the brand image course, specific integration strategies and teaching methods are proposed, and their feasibility and effectiveness are verified through case analysis and teaching practice